First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Feb. 27th, 1922. "Habit, Adaptation." E.D. MACNAMARA, F.R.C.P., M.R.C.S. March 6th, 1922. "Fatigue and Sleep." Sir ROBERT ARMSTRONG JONES, M.D. March 13th, 1922. "Mind and Body." Sir FREDERICK MOTT, K.B.E., M.D., F.R.S., F.R.C.P. March 20th, 1922. "Crime and Delinquency." W.A. POTTS, M.A., M.D. March 27th, 1922. "Mental Deficiency." A.F. TREDGOLD, M.R.C.S., L.R.C.P., F.R.S. A Special Series of six Lectures delivered at The Royal Society of Arts, John Street, Adelphi, London. "The Economy of Health and the Human side of Industry and Commerce. April 26th, 1922. "Productive Occupation and Industry as a Social Service. Prof. E. COLLIS, M.D., M.R.C.P. Professor of Preventive Medicine, University College of S. Wales and Monmouthshire. May 3rd, 1922. "Vocational Guidance, Selection and Training as a Prevention of Economic Waste." Dr. G. H. MILES, D.Sc. Assistant Director and Secretary, National Institute of Industrial Psychology. May 10th, 1922. "Industrial Life, its hours of Work, Fatigue and Rest Pauses.'' Prof. C. S. MYERS, M.D., Sc.D., F.R.S. Director of the National Institute of Industrial Psychology. May 17th, 1922. "Physical Conditions in Relation to Health and output." Sir THOMAS OLIVER, M.D., LL.D., F.R.C.P. Professor of Medicine in the University of Durham. May 24th, 1922. "Personal Hygiene and the Importance of Food and Sufficient Sleep, Standards of Living and Family Welfare. LEONARD HILL, M.D., F.R.S. May 31st, 1922. "The Country's Needs and how to meet them through Health in Relation to Industry and Commerce." ROBERT R. HYDE. Director of the Industrial Welfare Society. SOME OF THE SINGLE LECTURES DELIVERED Oct. 26th, 1920. Y.M.C.A. (H.-Q.). Prof. BENJAMIN MOORE, D.Sc,, F.R.S. "Health and Legislation." Dec. 7th, 1920. Shoreditch Town Hall (Probationers from Old Street Police Court). Dr. W.A. POTTS, of Birmingham. "Crime and Delinquency in their Relation to Health." Dec. 9th, 1920. Worcester Town Hall (Municipal Authorities). Dr. ERIC PRITCHARD. Dec. 9th, 1920. Given-Wilson Institute, Plaistow. Dr. MARY SCHARLIEB. "Parenthood." Dec. 14th, 1920. Y.M.C.A. (H.-Q.). Sir FREDERICK MOTT, K.B.E., M.D., F.R.S., F.R.C.P. "Eugenics." Dec. 16th, 1920. Islington Boy Scouts' Rally. Mr. E.B. TURNER. "Recreation and Physical Exercise.'' Feb. 1st, 1921. Shoreditch Town Hall (Probation Officers from Old Street Police Court). Miss PICTON-TURBERVILL. "Prostitution: How Voluntary Workers can help." Feb. 18th, 1921. Domestic London Teachers' Association. Dr. MARY SCHARLIEB. "Hygiene and Food in Relation to Children." Feb. 22nd, 1921. Y.M.C.A. (H.-Q.). Dr. C.J. BOND. "Some Causes of Moral and Physical Disease." March 2nd, 1921. Bryant & May's Y.M.C.A. Hut, Victoria. Mr. E.B. TURNER. "Recreation and Physical Exercise." March 15th, 1921. Y.M.C.A. Hut, Leicester Square. Mr. E.B. TURNER. "How to Keep Fit." April 19th, 1921. Y.M.C.A. (H.-Q.). Prof. ADAMI, C.B.E., M.D., F.R.S. "Racial Diseases." April 27th, 1921. Y.M.C.A. Shepherd's Bush Hut. Mr. E.B. TURNER. "How to Keep Fit." May 15th, 1921. Brotherhood Association, Southampton. Mr. E.B. TURNER, F.R.C.S. "Recreation and Physical Exercise." May 20th, 1921. Y.M.C.A. Montague Street, London, W.C. Mr. E.B. TURNER, F.R.C.S. "How to Keep Fit." June 1st, 1921. The Coalition Liberal Association, Old Gravel Pit Hall, Hackney. Hon. Organiser. "The People's League of Health: Its Aims and Objects." June 8th, 1921. Rotary Club, Brighton and Hove. Hon. Organiser. "The People's League of Health: Its Aims and Objects." Oct. 10th, 1921. Earl Shilton Branch of League, Leicestershire. C.W. SALEEBY, F.R.S.E. 14 200/B/3/2/C693/1/71